Investigation of the Potential Use of Curauá Fiber for Reinforcing Mortars - Afonso R. G. de Azevedo (Fibers, 2020)
Curauá is a bromeliad of Amazonian origin, present in some states in the northern region of Brazil and in other countries in South America. Its natural fibers have several technological advantages for application in composite materials. The objective of this research was to investigate the potential of using the fiber of Curauá as a reinforcement element in mortars for wall covering. Mortars were made with a 1:1:6 ratio (cement:lime:sand) in relation to their mass, evaluating the effect of adding 1%, 2% and 3% of Curauá fiber natural and fiber treated in NaOH solution in relation to the mass of cement, compared to the reference mixture (0%). Technological properties such as consistency, water retention and incorporated air content, compressive strength, water absorption and durability in wetting and drying cycles were evaluated. The results showed that the addition of the Curauá fiber causes an improvement in the mechanical properties of mortars, and at levels of addition 3% or more, it causes problems of workability and incorporation of air into the dough, thus, the fiber addition in 2% presented better results for application in coating mortars, in relation a Brazilian norm, even improving the durability of external coatings.